Cardiac resident nestin+ cells participate in reparative vascularisation1. Issue 9 (25th May 2013) - El‐Helou, Vivianne; Chabot, Andréanne; Gosselin, Hugues; Villeneuve, Louis; Clavet‐Lanthier, Marie‐Elaine; Tanguay, Jean‐Francois; Enikolopov, Grigori; Fernandes, Karl J.L.; Jasmin, Jean‐Francois; Calderone, Angelino
Abstract The rodent heart contains a population of nestin(+) cells derived from the embryonic neural crest and migrate to the scar after myocardial infarction (MI). The present study tested the hypothesis that intron 2 of the nestin gene drives expression and a subpopulation of nestin(+) cells participate in reparative vascularisation. The directed expression of the green fluorescent protein (GFP) by the second intron of the nestin gene identified GFP/nestin(+) cells intercalated among ventricular myocytes in the heart of normal transgenic mice. Ischemic injury led to the migration of GFP(+) cells to the scar and a subpopulation was detected in CD31/nestin(+) endothelial cells of newly formed blood vessels. The direct contribution to reparative vascularisation provided the impetus to test the hypothesis that increasing the population of nestin(+) cells in the infarcted heart will improve scar healing. Skin‐derived cells isolated from E18 Sprague–Dawley rats grew as spheres, expressed nestin, sox2, neural crest‐related transcriptional genes and a panel of peptide growth factors. Skin‐derived cells transplanted in the non‐infarcted left ventricle of 3‐day post‐MI rats migrated to the peri‐infarct/infarct region and remained engrafted for 21 days. A significantly smaller infarct, increased number of small calibre blood vessels and improved ventricular function were observed in engrafted infarcted rat hearts. Thus, the second intron of the nestin gene drives expression in the mouse heart and a subpopulation of GFP/nestin(+) cells directly participate in reparative vascularisation. Increasing the population of nestin(+) cells via the transplantation of skin‐derived cells represents a potential approach to limit ischemic damage to the heart. J. Cell. Physiol. 228: 1844–1853, 2013. © 2013 Wiley Periodicals, Inc.